MENINGKATKAN KEMAMPUAN MEMBACA HURUF HIJAIYAH MENGGUNAKAN METODE IQRO’ PADA SISWA TUNAGRAHITA KELAS IV DI SLB NEGERI LUTANG - Firmansyah, Firmansyah; Syamsuddin, Syamsuddin; Zulfitrah, Zulfitrah (-, 2025)
This study examines the ability to read hijaiyah letters using the Iqro' method for mentally retarded students at Lutang State SLB. The purpose of this study was to find out how the ability to read hijaiyah letters in mentally retarded students before and after using the Iqro' method and to find out the increase in hijaiyah reading ability in mentally retarded students. This research approach uses quantitative descriptive research so that researchers describe phenomena that occur in a real, realistic, actual manner which are described systematically. The ability to read hijjaiyah letters in mentally retarded students was carried out using a one group pretest-posttest design. The subjects of this study were mentally retarded students of class IV Lutang State SLB with a total sample of 3 students. Data was collected using oral tests and interviews. Descriptive data analysis technique. The results of this study indicate that the use of the Iqro method in improving the ability to read Hijaiyah letters in mentally retarded students has increased.